Multiple Giant Cell Tumors of Tendon Sheath Found within a Single Digit of a 9-Year-Old - John S. Hwang; Valerie A. Fitzhugh; Peter D. Gibson; Jacob Didesch; Irfan Ahmed (Case Reports in Orthopedics)
Giant cell tumor of tendon sheath is one of the most common soft tissue tumors of the hand. These tumors typically occur in the third or fourth decade of life and present as solitary nodules on a single digit. Currently, the greatest reported number of lesions found within a single digit is five. Although uncommon, giant cell tumor of tendon sheath does occur in the pediatric population. Herein we present a report of a rare case of GCTTS in a child in which seven lesions were identified within a single digit—the greatest number of lesions within a single digit reported to date.